Technology and Disintermediation in Online Marketplaces - Gu, Grace Y. (Management Science, 2024)
With the development of communication technology that makes online transactions easier, there is also an increased risk of disintermediation—sellers and buyers circumventing a platform to transact directly—in online two-sided marketplaces. Such disintermediation may lead to significant revenue loss for online platforms. However, it remains unclear how the characteristics of platforms affect their vulnerability to disintermediation. Using the blockade of Skype in mainland China as a natural experiment, this study examines how online communication technologies affect disintermediation and transaction outcomes in a large U.S. online freelance marketplace. The results show that restricting this alternative communication technology, which platforms struggle to monitor, reduces disintermediation by around 18%. This effect is potentially due to economic frictions in transactions, as the reduction in disintermediation is greater for high-transaction-cost jobs, such as time-sensitive jobs, communication-intensive jobs, and high-skilled jobs, as well as for cost-sensitive users, such as experienced users and personal users as opposed to enterprise users. With these results, platforms can reduce disintermediation risks when making investment and market entry decisions. This paper was accepted by D. J. Wu, information systems. Funding: This work was supported by the Strategic Management Society [SRF Dissertation Research Grant]. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2021.02736 .